Environmental cadmium exposure and the risk of kidney stones: a systematic review and dose-response meta-analysis - Ren, Zheng-Ju; Zhang, Qin; Tang, Na-Xian; Li, Ya-Dong; Lu, Dong-Liang; Lin, An-Long; Yang, Chuan; Wang, Feng (Frontiers in Medicine, 2025)
BackgroundRecent studies have investigated the relationship between cadmium exposure and kidney stones. Nevertheless, the results remain controversial. Therefore, we performed a comprehensive systematic review and meta-analysis based on the latest evidence to address gaps in the research.MethodsMedline, Embase, and the Web of Science databases were searched to identify relevant studies up until 31 July 2024. Characteristics and outcomes of the included studies were extracted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and the Meta-analyses of Observational Studies in Epidemiology (MOOSE) guidelines. A random effects model was used to determine the association between cadmium exposure and the risk of kidney stones.ResultsA total of 17 studies involving 159,011 individuals were included in the meta-analysis. When comparing the highest versus lowest cadmium exposure levels, the overall relative risk (RR) for kidney stones was 1.19 [95% confidence interval (CI): 1.10–1.29]. Subgroup analysis showed that urinary (RR = 1.19; 95%CI: 1.08–1.30) and blood (RR = 1.49; 95% CI: 1.10–2.02) cadmium levels were associated with an increased risk of kidney stones. In contrast to non-cadmium-contaminated areas, both blood (RR = 1.08; 95% CI: 1.00–1.15) and urinary (RR = 1.16; 95% CI: 1.05–1.27) cadmium levels were associated with an increased risk of kidney stones in cadmium-contaminated areas. In the dose–response meta-analysis, we observed a consistent linear positive association between cadmium exposure and the risk of kidney stones. The overall RR for every 1.0 μg/L increase in urinary cadmium levels was 1.07 (95% CI: 1.01–1.13).ConclusionOur findings suggest that cadmium exposure is associated with the risk of kidney stones. These findings reinforce the importance of environmental cadmium exposure as a risk factor for kidney stones, extending beyond the influence of conventional risk factors. Efforts to reduce cadmium exposure in the population may help reduce the individual, economic, and societal burdens associated with kidney stones.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero.